Konseling Behavioral dengan Teknik Reinforcement dan Punishment dalam Meningkatkan Kepatuhan Anak Autisme Spectrum Disorder di PAUD Inklusi Sidoarjo - Amriana, Amriana; Setiyani , Nonik; Oktasiana, Eka Tri; Azami, Firdaus; Nisrina, Hafshah Salsabila (Jurnal Bimbingan dan Konseling Islam, 2024)
This study aims to describe the implementation of behavioral counseling with reinforcement and punishment techniques to improve compliance among children with Autism Spectrum Disorder (ASD) at an inclusive preschool in Sidoarjo. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data were analyzed using thematic analysis techniques, involving data reduction, categorization, and interpretation to identify behavior patterns and intervention effectiveness. The study was conducted over five weeks on two twin children with ASD who exhibited different behavioral characteristics. Positive reinforcement was applied to increase adaptive behaviors such as task focus and compliance with instructions, using praise, thumbs-up gestures, and rewards. Results showed that this technique effectively enhanced the motivation and positive responses of both subjects. Punishment was used to reduce maladaptive behaviors, such as tantrums and hitting, by implementing consequences such as placing the child in a designated tantrum room. This technique was found effective in reducing the frequency of negative behaviors, especially when consistently implemented by teachers at school and supported by parents at home. This study provides practical contributions for teachers, counselors, and parents in creating a supportive learning environment through structured behavioral counseling applications. Collaboration between schools and families is crucial for the success of interventions, helping children with ASD develop their full potential.